STUDI ANALISIS EIGENFACE DAN EIGEN FUZZY SET UNTUK EKSTRAKSI CIRI BIBIR PADA SISTEM IDENTIFIKASI WAJAH - M. Rahmat Widyanto; Shinta Puspasari (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2008)
This paper compares the performance of eigenface and eigen fuzzy set to extract lip traits. Testing is conducted by implementing the two methods in a face identification system based on lip traits. The database used is primary data that consists of front-face image and lip image. The test result shows that eigenface is more effective with average precisionrecall value 0.22% higher. However, statistical tests show that there are no significant differences between the two methods. An optimal extraction method will be used to develop face identification system based on facial components.